2011
DOI: 10.1021/jp2083456
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Dependence of 3JCH Coupling Constants in 2-Substituted 4-t-Butyl-cyclohexanone and Their Alcohol Derivatives

Abstract: Theoretical and experimental studies on (3)J(C2H6eq) NMR spin-spin coupling constants in both the 2-X-4-t-butyl-cyclohexanone (X = H, CH(3), F, Cl, and Br) and in their alcohol derivatives series are reported. Results thus found are rationalized in terms of the transmission of the Fermi contact contribution to such couplings. To this end, dependencies of (3)J(C2H6eq) couplings versus the C(2)-C(1)-C(6) angle are compared in both series for equatorial and axial X orientations. The main trend is described in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In the particular case of 2 J FF SSCCs in fragments of type F–C–F very important contributions originating in the PSO and SD terms are known, and they are surprisingly sensitive to electron-withdrawing groups bonded to the intermediate C atom. , To understand factors determining such unusual trends, in this study we applied a semiqualitative approach, reported previously, specially suited to understand electronic factors originating trends of high-resolution NMR parameters. As shown below, when applying this model, it is predicted that the isotropic value of either the PSO or the SD terms may depend rather strongly on the angles formed by each C–F bond containing the coupling nuclei and the eigenvectors of the respective tensors.…”
Section: Introductionmentioning
confidence: 99%
“…In the particular case of 2 J FF SSCCs in fragments of type F–C–F very important contributions originating in the PSO and SD terms are known, and they are surprisingly sensitive to electron-withdrawing groups bonded to the intermediate C atom. , To understand factors determining such unusual trends, in this study we applied a semiqualitative approach, reported previously, specially suited to understand electronic factors originating trends of high-resolution NMR parameters. As shown below, when applying this model, it is predicted that the isotropic value of either the PSO or the SD terms may depend rather strongly on the angles formed by each C–F bond containing the coupling nuclei and the eigenvectors of the respective tensors.…”
Section: Introductionmentioning
confidence: 99%